The Use of New Phraseological Units and Collocations in the Language - Navruza Alieva (Central Asian Journal of Literature, Philosophy and Culture, 2022)
This article reveals the role of the Internet and computer technologies on the way to the emergence of new subsystem - Internet phraseology, with its corresponding units - neo-phraseological units. The changes that the language undergoes under the influence of new phraseological units are noted and signs of such neoformations are highlighted. Also, an analysis of the considered works on research in three different system languages is presented, various examples of traditional and Internet phraseological units found on the network are given. In the process of studying the work of foreign and domestic researchers, questions were identified for further analysis.